قراءة توحيدية في حديث افتراق الأمة - عامر الحافي (International Institute of Islamic Thought, 2011)
أمام العديد من القراءات التفريقية السائدة لحديث افتراق الأمة، التي تكرس الفرقة وتشيع الفتنة والصراع بين أبناء أمة التوحيد، تظهر الحاجة الملحة لدراسة هذا الحديث دراسة توحيدية على ضوء القرآن الكريم والسنة النبوية، ومحاولة الخروج بقراءة معاصرة للعلاقة بين الفرق الإسلامية تعظم الجوامع وتبحث عن الكلمة السواء. فادعاء تفرد فرقة معينة من المسلمين بالنجاة وبهلاك أتباع الفرق الأخرى يوشك أن يكون ظاهرة عامة في تاريخ الفرق الإسلامية. وأمام هذه الإشكالية يسعى هذا البحث إلى دراسة مرتبة الحديث والمعاني الأساسية لمتنه، وتناول الفرق الإسلامية المختلفة له، والمقصود بالأمة في نص الحديث، والدلالات الخاصة بعدد الفرق المذكور في الحديث، وإمكانية تعيين الفرقة الناجية، وخطورة القراءة التفريقية في دراسة الفرق الإسلامية، وأبرز ملامح القراءة التوحيدية في هذه الدراسة    Unlike most of the prevailing readings of the "Hadith of sects of Muslim Ummah", which establishes a discord and conflict that disturbs the unity of Muslims, there is an urgent need to study this Hadith differently, to give a better understanding of the relationship between Muslim sects; an understanding that maximizes denominators and common word. The claim of uniqueness of a certain sect to be right and to consider others to be wrong and deserves hell, is about to be a general phenomenon in the history of Muslim sects. This paper aims to explain the reliability of the Hadith and its meanings, the way in which the Hadith addresses the difference between the various Muslim groups, the indicators related to the number of groups, the possibility of identifying the right one, the dangers of the sectarian reading of the Hadith, and main features of a monotheistic reading of the study of Muslim sects.